Alleviation of C⋅C Mismatches in DNA by the Escherichia coli Fpg Protein - Tesfahun, Almaz Nigatu; Alexeeva, Marina; Tomkuvienė, Miglė; Arshad, Aysha; Guragain, Prashanna; Klungland, Arne; Klimašauskas, Saulius; Ruoff, Peter; Bjelland, Svein (Frontiers in Microbiology, 2021)
DNA polymerase III mis-insertion may, where not corrected by its 3´ → 5´ exonuclease or the mismatch repair (MMR) function, result in all possible non-cognate base pairs in DNA generating base substitutions. The most thermodynamically unstable base pair, the cytosine (C)C mismatch, destabilizes adjacent base pairs, is resistant to correction by MMR in Escherichia coli, and its repair mechanism remains elusive. We present here in vitro evidence that CC mismatch can be processed by base excision repair initiated by the E. coli Fpg protein. The kcat for CC is, however, two orders of magnitude lower than for its primary substrate 8-oxoguanine (oxo8G)C, and one order of magnitude lower than for 5,6-dihydrothymine (dHT)C and thymine glycol (Tg)C. The KM values are all in the same range, which indicates efficient recognition of CC mismatches in DNA. Fpg activity was also exhibited for the thymine (T)T mismatch and for N4- and/or 5-methylated C opposite C or T, Fpg activity being enabled on a broad spectrum of DNA lesions and mismatches by the flexibility of the active site loop. We hypothesize that Fpg plays a role in resolving CC in particular, but also other pyrimidinepyrimidine mismatches, which increases survival at the cost of some mutagenesis.